Pengembangan POC Limbah Ternak Kambing dan POC Paitan (Tithonia Diversifolia) serta Efektivitasnya pada Tanaman Mentimun (Cucumis Sativus L.) - Fenniati Panggalo; Vianti Mesa; Adewidar M. Pata’dungan; Sepsriyanti Kannapadang; Willy Y. Tandirerung (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This research aims to develop liquid organic fertilizer (LOF) made from goat livestock waste and paitan (Tithonia diversifolia) conducted in Makale, Tana Toraja Regency, from March to June 2025. This study aims to determine the response of cucumber plants to the application of LOF derived from the combination of goat livestock waste and paitan plants. Goat livestock waste contains macro nutrients such as nitrogen (N), phosphorus (P), and potassium (K), while paitan plants are green organic materials rich in nutrients and easily decomposed. The combination of both is expected to naturally improve soil fertility and optimally support the growth and yield of cucumber plants. The research method uses a Completely Randomized Design (CRD) with four different LOF concentration treatments and five replications. Parameters observed include plant height, number of leaves, stem diameter, number of flowers, number of fruits, and fruit weight per plant. The LOF production process is carried out through fermentation for 21 days with a ratio of goat livestock waste and paitan of 3:1, and the addition of EM4 as a microorganism activator. This research also aims to evaluate the effectiveness of LOF application on growth parameters (plant height, number of leaves) and yield (number and weight of fruits) of cucumber plants, and compare it with treatments without LOF or with inorganic fertilizers. The results of this research are expected to serve as a reference for local farmers in developing organic fertilizers based on local resources that are environmentally friendly, efficient, and sustainable to increase agricultural productivity in the Tana Toraja region.